Trends in prevalence of cerebral palsy in children born with a birthweight of 2,500 g or over in Europe from 1980 to 1998. - Sellier, E; Surman, G; Himmelmann, K; Andersen, G; Colver, A; Krägeloh-Mann, I; De-la-Cruz, J; Cans, C (2010)
Time trends for cerebral palsy (CP) prevalence in children born > or =2,500 g vary across studies and scarce data exist on trends by subtype of CP. The objective of this study was to describe changes in prevalence of CP in infants born > or =2,500 g between 1980 and 1998 in Europe. Data were collated from the SCPE (Surveillance of Cerebral Palsy in Europe collaboration) common database. Poisson regression was used to test for change in prevalence over time. Birth year and register effects were explored and trends in prevalence were estimated by CP subtype and severity. Four thousand and two children with CP and birthweight > or =2,500 g were recorded in 15 population based-registers. The overall prevalence of CP was 1.16 per 1,000 live births (99% CI, 0.88-1.48) in 1980 and 0.99 (CI, 0.80-1.20) in 1998. The trend was not significant (P = .14), except in two registers. However, there were significant changes in the prevalence of spastic CP subtypes, with a decrease in the bilateral spastic form (P < .001), and an increase in the unilateral spastic form (P = .004). There was a concurrent reduction in neonatal mortality of children with birthweight > or =2,500 g: from 1.7 (CI, 1.4-2.1) to 0.9 (CI, 0.7-1.1) per 1,000 live births. In conclusion, for children born with birthweight > or =2,500 g, the prevalence of CP in Europe was stable in spite of changes by subtype and a significant decrease in neonatal mortality.